The effect of digital literacy to internet addiction - Raymond Frans Deonisius; Ika Lestari; Sarkadi Sarkadi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
The purpose of this study was to investigate the effect of digital literacy to internet addiction. For this purposed, we conducted a survey from 347 participants of middle school students at Menteng sub-district, Central Jakarta. This study was used a simple regression equation model to evaluate the structural model. The result showed that digital literacy positively significant affected internet addiction. Digital literacy simultaneously had a positive significant effect to internet addiction.